(untitled) (Research, Society and Development, 2022)
In this text, we discuss that torture against militant women and prisoners during the military dictatorship in Brazil (1964-1985) has above all gender specificities. In the testimonies of the five women activists we studied, based on their reports in the National Commission and Regional Truth Commissions, it is evident that brutal crimes of a sexual and gender nature, of use and abuse of the female body, have become a legitimate and institutionalized practice. by the military government. A finding that has also occurred in other studies about dictatorial contexts, despite still being an approach to be further researched. Thus, the testimonies also demonstrate that these women continue to care for their memories and political trajectories. Torture and gender violence are still present in their memories, but they did not intimidate or prevent them from putting gender alterity and their individual-collective memories in the service of truth and justice.